The phosphocholine and glycerophosphocholine content of an oestrogen-sensitive rat mammary tumour correlates strongly with growth rate - Smith, T A; Eccles, S; Ormerod, M G; Tombs, A J; Titley, J C; Leach, M O (British journal of cancer, 1991)
An oestrogen sensitive rat mammary tumour was grown in two groups of female and one group of male hooded rats. The male group and one of the female groups were supplemented with oestrogen. The tumours grew most rapidly in the female supplemented group. When the tumours reached 1.5 cm in diameter they were harvested and the cell cycle distribution and number of cells actively synthesising DNA (bromodeoxyuridine (BrdU) labelling index) determined in each case. Chemical extracts were prepared from each tumour and the concentration of phosphorus-containing metabolites determined using high resolution NMR spectroscopy. The concentration of phosphocholine was found to correlate strongly with the number of cells in S-phase and the number of cells labelled with BrdU, whilst a highly significant negative correlation was observed between these two parameters and glycerophosphocholine. The concentration of phosphoethanolamine did not correlate with either of these measures of proliferation rate. The concentration of glycerophosphorylethanolamine showed a weak negative correlation with the number of cells in S-phase.